Realization of Learning Islamic Education Through Multimedia at Madrasah Aliyah Negeri 3 Indragiri Hilir - Ardila, Eka; Hidayah, Siti (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2023)
Purpose of the study: The purpose of this study was to determine the realization of learning Islamic Education through class X multimedia at Madrasah Aliyah Negeri 3 Indragiri Hilir, and the factors that influence it. Methodology: This type of research is a quantitative descriptive research. The population in this study were 4 teachers of Islamic Religious Education at Madrasah Aliyah Negeri 3 Indragiri Hilir. The data in this study were collected using observation techniques and documentation. Furthermore, the collected data was analyzed using the percentage formula. Main Findings: The results of data analysis through observation can be summarized as follows: The realization of Islamic Religious Education learning through multimedia at Madrasah Aliyah Negeri 3 Indragiri Hilir, reached 82.5%. The influencing factors are as follows: The work steps carried out by the teacher in the teacher's difficulties in preparing multimedia learning. Teachers find it difficult to reply and read chats from students, which are large in number on one mobile phone (HP). Internet networks are often constrained so that it can complicate online-based learning activities. There are a small number of students who cannot participate in learning activities properly, because their Android cellphone (HP) is not in adequate condition. Novelty/Originality of this study: Based on the research conducted, by conducting this research it is known that the realization of Islamic Religious Education learning through multimedia at Madrasah Aliyah Negeri 3 Indragiri Hilir is categorized as good.